2020
DOI: 10.1186/s13024-020-0358-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approaches targeting Apolipoprotein E function in Alzheimer’s disease

Abstract: One of the primary genetic risk factors for Alzheimer's disease (AD) is the presence of the Ɛ4 allele of apolipoprotein E (APOE). APOE is a polymorphic lipoprotein that is a major cholesterol carrier in the brain. It is also involved in various cellular functions such as neuronal signaling, neuroinflammation and glucose metabolism. Humans predominantly possess three different allelic variants of APOE, termed E2, E3, and E4, with the E3 allele being the most common. The presence of the E4 allele is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 240 publications
0
89
0
1
Order By: Relevance
“…Cholesterol homeostasis was impaired in AD as well [20]. One of the primary risk factors for AD is the presence of apolipoprotein E (APOE), a polymorphic lipoprotein that mainly carries cholesterol in the brain [21]. There are three major APOE alleles in humans, among which APOE 2 allele is closely associated with the reduced risk of AD, while APOE 4 allele devotes much to AD occurrence [22].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Cholesterol homeostasis was impaired in AD as well [20]. One of the primary risk factors for AD is the presence of apolipoprotein E (APOE), a polymorphic lipoprotein that mainly carries cholesterol in the brain [21]. There are three major APOE alleles in humans, among which APOE 2 allele is closely associated with the reduced risk of AD, while APOE 4 allele devotes much to AD occurrence [22].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…While apoE isoforms can directly affect Alzheimer’s neuropathology, including the accumulation of amyloid-β (Aβ) and tau, increasing evidence has demonstrated that apoE isoforms also contribute to cognitive function through AD neuropathology-independent pathways ( Liu et al, 2013 ; M. Di Battista et al, 2016 ; Montagne et al, 2020 ; Yamazaki et al, 2020 ). These effects might be mediated by apoE-regulated lipid metabolism, synaptic function, vascular integrity, and/or neuroinflammation ( Liu et al, 2013 ; M. Di Battista et al, 2016 ; Montagne et al, 2020 ; Yamazaki et al, 2020 ; Williams et al, 2020 ; Najm et al, 2019 ). Recently, by performing both clinical and preclinical analysis, we showed that APOE2 protects against age-associated cognitive decline independent of AD neuropathology.…”
Section: Introductionmentioning
confidence: 99%
“…These studies with the MMP9KO mice provide a simplified view of the deleterious actions of MMP-9 in AD and the benefits associated with inhibiting it, without the complexity of apoE ~ 137 ~ isoforms. However, apoE-driven AD pathologies differ from pure amyloid pathologies [525], [526] and, as detailed in this thesis, apoE can modulate multiple aspects of MMP-9 regulation other than elevated expression and may still influence MMP-9 disposition after its induction. Hence, it would be interesting to build on these in vivo studies and cross MMP9KO mice with EFAD mice, to generate EFAD mice in which the MMP-9 gene is deleted.…”
Section: Chapter 6: Future Directionsmentioning
confidence: 90%